Parents’ influence on ESL learners’ English language proficiency - Singh, Sukhdeep (2023)
This study investigated the correlation between parental involvement and ESL learners' English language proficiency. Using a quantitative methodology, Gardner (2004)-adapted surveys were given to 111 utar Kampar students in the faculty of social science (FAS). The analysis's findings showed that among ESL learners, parental influence and language proficiency were significantly positively correlated. The results supported previous research highlighting the critical role parents play in their children's language development by showing that students with high language proficiency reported higher levels of parental involvement. In the discussion of the results, Vygotsky's zone of proximal development (ZPD) and Bronfenbrenner's ecological systems theory were highlighted for their theoretical significance.